Controlled Synthesis of Silver Nanoparticles Using Double Reductants and Its Voltammetric Characteristics Study - Yubo Duan; Zhihua Xu; Xiaochun Jiang (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Constructing robust silver nanoparticles (AgNPs) with good shape and dispersibility is of particular interest in analytical applications. Herein, monodispersibility AgNPs with the average size of 20 nm have been successfully prepared via one-pot method using sodium borohydride and trisodium citrate as co-reductants. The introduction of sodium borohydride greatly accelerated the rate of nucleation, which can effectively solve the problem of broad size distribution. Both shape and dispersibility of AgNPs can be effectively adjusted by simple control of refluxing time or concentrations of the sodium borohydride. We also studied the voltammetric characteristics of the AgNPs using Ag/AgCl solid-state voltammetry. An intense and stable current peak at a low potential could be obtained, which could provide a unique advantage in analytical applications.